Commissioning and validation of the electron Monte Carlo dose calculation at extended source to surface distance from a medical linear accelerator - Arunkumar T.; Varatharaj C.; Ravikumar M.; Ganesh K.M.; S. Sathiyan; Shwetha B (International Journal of Medical Research and Review, 2016)
Introduction: Radiotherapy is one of the major modality for cancer management playing curative, adjuvant, and palliative and sometimes has an alternative role to chemotherapy. Radiotherapy is practiced in two ways viz. External beam therapy and Brachytherapy. Electron beam therapy is widely used in the management of cancers. An electron beam is characterized by a finite range of penetration with a rapid dose fall off towards a slowly decaying x-ray background as the electrons traverse through tissues. The electron monte carlo (eMC) dose calculation algorithm for eclipse treatment system has been introduced by Varian Medical systems. The algorithm is commissioned and validated by comparing percentage depth dose (PDD) and gamma index.Methods: Percentage depth dose curves were generated for all the energies for 4x4 cm2 and 10x10 cm2 field sizes. The depth of maximum dose (R100), therapeutic depth (R85), depth of 50% isodose (R50) and the relative surface (Ds) were compared with the measured and calculated PDD curves.Results: The eMC calculated fluence and measured fluence were compared for all the energies and cones at nominal source to surface distance and extended distances. For 4x4 cm2 field size the maximum shift in R100 was 5 mm, R85 was 1.9 mm, R50 was 0.9 mm and the variation in the relative surface (DS) was about 25Gamma analysis shows excellent agreements with greater than 98% of the pixels passing the gamma requirements.Conclusion: We have successfully commissioned and validated the electron monte carlo dose calculation at extended source to surface distance.